The Efforts to Strengthen the Understanding of Religious Anti-Radicalism Among Students in College - Akbar Nur Aziz; Mahli Zainuddin Tago (State Institute of Islamic Studies (IAIN) Salatiga, 2023)
This paper aims to provide an explanation regarding the interpretation of religious radicalism, the dangers of religious radicalism in higher education, as well as the views of Muhammadiyah and Nahdlatul Ulama on religious radicalism. This research uses a literature review method with a descriptive qualitative approach. This paper shows the results that in the results of the pretest understanding of religious radicalism in undergraduate students of Agribusiness, Faculty of Agriculture, UMY still have an insufficient understanding or around 66.3%. After being given an explanation regarding the material for understanding radicalism, the posttest showed different results, namely rising to 94% of students understanding the meaning and dangers of radicalism in the higher education environment. This shows that undergraduate students of Agribusiness, Faculty of Agriculture, UMY have a complete understanding of religious radicalism. It is hoped that students will have shields so that they are not exposed to the virus of religious radicalism that attacks the university environment. Several steps in efforts to prevent radicalism in the tertiary environment include understanding religious moderation in lectures, holding religious discussions, and preventive and rehabilitative measures.